Dynamic Variations in Soil Properties in Different Land Use Types in Doti District, Nepal - Shahi, Jitendra Bikram; Dahal, Bed Mani; Raut, Nani; Giri, Dhiraj (Journal of Nepal Chemical Society, 2026)
Soil quality is one of the primary factors influencing how many and what kind of crops can be grown and what success ecosystems will have over the long term. Knowledge about how gradients of agroecology and land-use systems affect soil quality is essential in proposing sustainable farming practices. This study assesses the spatial variability of selected physical and chemical properties of soil across three ecological zones—lowland, midland, and highland—and three land use types: traditional agricultural practice, commercial vegetable cultivation, and barren land. The research was carried out in the Doti district of Nepal. A total of 144 soil samples were collected from four depths (0-15, 15-30, 30-60, and >60 cm intervals) for the purpose and were then tested for temperature, moisture, bulk density, pH, total nitrogen, available potassium, available phosphorus, organic carbon, and cation exchange capacity. The data collected indicated a significant variousness (p < 0.05) of characteristics under different land uses, signifying that chemically all the land-use types were chemically variable in nature. Another low value witnessed was in the bulk density of the soils, which was 0.88±0.04 g/cm3. This means that the structure and nutrients will be better due to the high amount of organic matter. The highest organic carbon and cation exchange capacity were in the highland zones. In contrast, the barren land soils had a trend indicating a decline in nutrient status and increasing compaction and acidity. Nutrient concentration significantly decreased with increasing depth, pointing to the fact that the most sensitive layer to management changes is the uppermost layer. The study emphasized the need to develop zone-specific soil management strategies, through which one seeks to enhance the organic matter available in soil, protect against erosion, and achieve sustainable intensification to make the soil resilient and productive in agriculture in the case of Doti.